The body in transformative learning - Christine Joanna Schlattner (Adult Education Research Conference, 1994)
In Transformative Dimensions of Adult Learning, Jack Mezirow advances a theory of transformative learning. He focuses on rational, critical reflection as the primary means for this change. This research explores the role the body may play in transformative learning.